Prolonged Cardiac Rhythm Monitoring and Secondary Stroke Prevention in Patients With Cryptogenic Cerebral Ischemia. Issue 8 (August 2019) - Tsivgoulis, Georgios; Katsanos, Aristeidis H.; Grory, Brian Mac; Köhrmann, Martin; Ricci, Brittany A.; Tsioufis, Konstantinos; Cutting, Shawna; Krogias, Christos; Schellinger, Peter D.; Campello, Ana Rodriguez; Cuadrado-Godia, Elisa; Gladstone, David J.; et al.
Abstract : Background and Purpose—: Although prolonged cardiac rhythm monitoring (PCM) can reveal a substantial proportion of ischemic stroke (IS) patients with atrial fibrillation not detected by conventional short-term monitoring, current guidelines indicate an uncertain clinical benefit for PCM. We evaluated the impact of PCM on secondary stroke prevention using data from available to date randomized clinical trials and observational studies. Methods—: We performed a comprehensive literature search in MEDLINE, SCOPUS, CENTRAL (Cochrane Central Register of Controlled Trial), and conference proceedings to identify studies reporting stroke recurrence rates in patients with history of cryptogenic IS or transient ischemic attack (TIA) receiving PCM compared with patients receiving conventional (non-PCM) cardiac monitoring. Results—: We included 4 studies (2 randomized clinical trials and 2 observational studies), including a total of 1102 patients (mean age: 68 years, 41% women). We documented an increased incidence of atrial fibrillation detection (risk ratio=2.46; 95% CI, 1.61–3.76) and anticoagulant initiation (risk ratio=2.07; 95% CI, 1.36–3.17) and decreased risk of recurrent stroke (risk ratio=0.45; 95% CI, 0.21–0.97) and recurrent stroke/TIA (risk ratio=0.49; 95% CI, 0.30–0.81) during follow-up for IS/TIA patients who underwent PCM compared with IS/TIA patients receiving conventional cardiac monitoring. In the subgroup analysis, according to study type, atrial fibrillation detection, anticoagulant initiation, and IS/TIA recurrence rates were comparable between PCM and non-PCM in randomized clinical trials and observational studies. No evidence of heterogeneity ( I 2 <12%) was documented across all the aforementioned subgroups. Conclusions—: We provide preliminary evidence for a potential impact of PCM on secondary stroke prevention, as patients with cryptogenic IS/TIA undergoing PCM had higher rates of atrial fibrillation detection, anticoagulant initiation, and lower stroke recurrence. Abstract : Supplemental Digital Content is available in the text.